2017
DOI: 10.1038/jhg.2017.32
|View full text |Cite
|
Sign up to set email alerts
|

Intragenic multi-exon deletion in the FBN1 gene in a child with mildly dilated aortic sinus: a retrotransposal event

Abstract: Marfan syndrome is an autosomal dominant disorder affecting mainly the skeletal, ocular and cardiovascular systems. Most cases are caused by mutations in the fibrillin-1 gene (FBN1), although there are some reports on deletions involving FBN1 and other additional genes. We report a male patient who was first evaluated at 4 years of age. Echocardiogram showed a mildly dilated aortic sinus. He also had a history of muscular ventral septal defect which was closed spontaneously and trivial mitral regurgitation. Ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…44 The spectrum of diseases that have been reported in relation to SVA transposition, including Marfan syndrome, hemophilia B, neurofibromatosis types 1 and 2, leukemia, and congenital muscular dystrophy, has been increasing progressively. [45][46][47][48][49][50] In this study, we report a homozygous CNV that is generated by an SVA transposition event and causes MMAF, leading to male infertility.…”
Section: Efficiency Of Wes To Detect Pathological Cnvs and Importancementioning
confidence: 87%
“…44 The spectrum of diseases that have been reported in relation to SVA transposition, including Marfan syndrome, hemophilia B, neurofibromatosis types 1 and 2, leukemia, and congenital muscular dystrophy, has been increasing progressively. [45][46][47][48][49][50] In this study, we report a homozygous CNV that is generated by an SVA transposition event and causes MMAF, leading to male infertility.…”
Section: Efficiency Of Wes To Detect Pathological Cnvs and Importancementioning
confidence: 87%
“…MAST2, as a microtubule associated kinase, plays important roles in a wide range of life activities. Previous studies have reported the role of MAST2 in evolution 12 , marfan syndrome 13 , neurodegeneration 14 , rabies virus infection 15 , nonobstructive azoospermia 16 , experimental autoimmune encephalomyelitis 17 , chronic myeloid leukemia 18 and breast cancer 4 . Our studies showed the abnormal expression and prognostic effects of MAST2 in liver cancer, which broadened the field of scientific research on MAST2.…”
Section: Discussionmentioning
confidence: 99%
“…A deletion of three FBN1 exons (7–9) from intron 6 to intron 9, spanning approximately 38.6 kb at 15q21.1 with a concomitant SVA F1 insertion, was identified in a study of a child with mildly dilated aortic sinus (Figure 1(c)). 44 Mutations in the FBN1 gene typically result in an autosomal dominant connective tissue disorder termed Marfan syndrome (MFS), which affects the skeletal, cardiovascular, and ocular systems. 62 In this case, the child displayed no other features indicative of an MFS diagnosis.…”
Section: Sva Insertions Associated With Large Genomic Deletionsmentioning
confidence: 99%